CON4EI: Development of testing strategies for hazard identification and labelling for serious eye damage and eye irritation of chemicals. (June 2018) - Adriaens, E.; Verstraelen, S.; Alépée, N.; Kandarova, H.; Drzewiecka, A.; Gruszka, K.; Guest, R.; Willoughby, J.A.; Van Rompay, A.R.
Abstract: Assessment of acute eye irritation potential is part of the international regulatory requirements for safety testing of chemicals. In the last decades, many efforts have been made in the search for alternative methods to replace the regulatory in vivo Draize rabbit eye test (OECD TG 405). Success in terms of complete replacement of the regulatory in vivo Draize rabbit eye test has not yet been achieved. The main objective of the CEFIC-LRI-AIMT6-VITO CON4EI (CONsortium for in vitro Eye Irritation testing strategy) project was to develop tiered testing strategies for serious eye damage and eye irritation assessment that can lead to complete replacement of OECD TG 405. A set of 80 reference chemicals ( e . g . balanced by important driver of classification and physical state), was tested with seven test methods. Based on the results of this project, three different strategies were suggested. We have provided a standalone (EpiOcular ET-50), a two-tiered and three-tiered strategy, that can be used to distinguish between Cat 1 and Cat 2 chemicals and chemicals that do not require classification (No Cat). The two-tiered and three-tiered strategies use an RhCE test method (EpiOcular EIT or SkinEthic™ EIT) at the bottom (identification No Cat) in combination with the BCOP LLBO (two-tiered strategy) or BCOP OP-KIT and SMI (three-tiered strategy) at the top (identification Cat 1). For our proposed strategies, 71.1% - 82.9% Cat 1, 64.2% - 68.5% Cat 2 and ≥ 80% No Cat chemicals were correctly identified. Also, similar results were obtained for the Top-Down and Bottom-Up approach. Highlights: CON4EI: CONsortium for in vitro Eye Irritation testing strategy (TS) develop TS for assessment of serious eye damage/eye irritation 80 reference chemicals balanced by driver of classification and physical state Seven test methods were evaluated. Proposed TS's: a standalone, a two-tiered and three-tiered strategy